The relationship between waist-to-height ratio, health-related physical fitness, and metabolic disease factors in middle-aged men in South Korea - Jung-Wook Lee; Gi-Chul Ha; Tae-Jin Kwak (Journal of Men's Health, 2025)
Background: The purpose of this study was to analyze the correlation between waist-to-height ratio (WHtR), health-related physical fitness, and metabolic disease risk factors in middle-aged men and to evaluate the impact of WHtR on these variables to validate its utility as an obesity index. Methods: A total of 1012 middle-aged men aged 30 to 60 years (205 in their 30s, 408 in their 40s, 319 in their 50s and 80 in their 60s) were selected as participants and classified into high and low WHtR groups based on a threshold of 0.5. The study variables included physical characteristics, health-related physical fitness (muscular strength, muscular endurance, flexibility and cardiorespiratory endurance), and metabolic disease factors (diastolic blood pressure, triglycerides, hemoglobin A1c, Triglyceride/High-Density Lipoprotein-Chlesterol ratio (TG/HDL) and Low-Density Lipoprotein-Cholesterol (LDL-C)). Group comparisons and multiple regression analyses were performed. Results: The results showed that the high WHtR group had significantly lower muscular endurance, flexibility and cardiorespiratory endurance but higher muscular strength than the low WHtR group. Additionally, the high WHtR group exhibited significantly higher diastolic blood pressure, triglycerides, glycated hemoglobin, and TG/HDL ratio than the low WHtR group (p < 0.05). Multiple regression analysis indicated that WHtR was significantly negatively correlated with cardiorespiratory endurance and muscular endurance, while it showed a significant positive correlation with TG/HDL ratio, glycated hemoglobin, diastolic blood pressure and LDL-C (p < 0.05). Conclusions: These findings suggest that WHtR is closely related to decreased physical fitness and increased metabolic disease risk in middle-aged men and can serve as a useful index for predicting obesity-related health risks.